Pendekatan Penelitian Kualitatif - Andi Supriandi (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Choosing the right research approach is one of the important steps that must be considered by a researcher. Researchers must choose a research approach that is in accordance with the desired data and results by considering that the research is relevant to the expected objectives, the validity and reliability of the results, the use of appropriate sources, data analysis in accordance with the research design, and other standards that make the research results quality. One approach that is often used in research by a researcher is qualitative. Qualitative research is a research approach used to understand social and cultural phenomena. Qualitative research methods allow researchers to collect in-depth and contextual data about the experiences and perceptions of individuals or groups that are sometimes different from what is seen by the eye. This article will discuss the qualitative research approach, including the types of research in the qualitative research approach. This research uses data collection techniques such as interviews, observations, and document analysis to collect rich and contextual data. The results of qualitative research can be used to better understand social and cultural phenomena and can be used as a basis for developing theories and interventions.